The Light of the Hidden Flowers - Dutta, Akash (Poetry of Bengal Ser., 2021)
Light blooms as our grass-birth arises from the infinite depth of our memories. Some immigrant dreams, however, roam around the courtyards of the illusive past in the darkness.These poems by Akash are intense in their unique sensitivities, eager in their search of the submerged consciousness and incomparably deft in turning words into hymns.